2012
DOI: 10.1007/s11033-012-2240-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of the apolipoprotein M gene polymorphisms and serum lipid levels

Abstract: The association of rs707921 and rs707922 SNPs in the apolipoprotein M (APOM) gene and serum lipid levels is still controversial. This study aimed to detect the association of the APOM rs707921 and rs707922 SNPs and several environmental factors with serum lipid profiles. Genotyping of rs707921 and rs707922 was performed in 703 of Mulao's and 707 of Han's participants. The serum levels of TG in Mulao, and TG and HDL-C in Han were different between the A and C allele carriers of rs707921 (P < 0.05-0.01); while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…All determinations were performed with an autoanalyzer (Type 7170A; Hitachi Ltd., Tokyo, Japan) in the Clinical Science Experiment Center of the First Affiliated Hospital, Guangxi Medical University. The normal values of serum TC, TG, HDL-C, LDL-C, ApoA1 and ApoB levels and the ratio of ApoA1 to ApoB in our Clinical Science Experiment Center were 3.10–5.17, 0.56–1.70, 1.16–1.42, 2.70–3.10 mmol/L, 1.20–1.60, 0.80–1.05 g/L and 1.00–2.50, respectively2122.…”
Section: Methodsmentioning
confidence: 82%
See 3 more Smart Citations
“…All determinations were performed with an autoanalyzer (Type 7170A; Hitachi Ltd., Tokyo, Japan) in the Clinical Science Experiment Center of the First Affiliated Hospital, Guangxi Medical University. The normal values of serum TC, TG, HDL-C, LDL-C, ApoA1 and ApoB levels and the ratio of ApoA1 to ApoB in our Clinical Science Experiment Center were 3.10–5.17, 0.56–1.70, 1.16–1.42, 2.70–3.10 mmol/L, 1.20–1.60, 0.80–1.05 g/L and 1.00–2.50, respectively2122.…”
Section: Methodsmentioning
confidence: 82%
“…It has been noted that the genotype and allele frequencies of several SNPs are not consistent among different populations8919202122. The G allele frequency of MLXIPL rs3812316 (Q241H) SNP was 0.05 in Mexicans41, 0.10 in Europeans18 and 0.09 in Indian Asians18 and Japanese individuals23.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results have recently been supported by evidence in plasma of humans (Plomgaard et al 2009) while others have found that human APOM gene variation affects HDL cholesterol (Park et al 2013;Aung et al 2013). Through carrying sphingosine-1-phosphate with effects on angiogenesis, endothelial cell migration, and inflammation, apoM (Christoffersen and Nielsen 2013) may be a link to many of the functions that are attributed to HDL.…”
Section: Apolipoprotein Mmentioning
confidence: 82%